Congestive heart failure in the pediatric patient with congenital heart disease. Issue 1 (February 2008) - Everitt, Melanie D; Yetman, Anji T
Congestive heart failure (CHF) is a general term referring to the constellation of signs and symptoms that result from decreased cardiac output. Such signs and symptoms may relate directly to a lack of systemic blood flow, pulmonary venous congestion and/or pulmonary arterial overcirculation. CHF may occur in childhood secondary to a variety of congenital structural cardiac lesions, congenital or acquired abnormalities of heart rhythm or impairment in myocardial function. This review will focus on CHF as it pertains to failure of the systemic ventricle in the setting of congenital cardiac defects.